Hemodynamic Effects, Safety, and Feasibility of Intravenous Esmolol Infusion During Takotsubo Cardiomyopathy With Left Ventricular Outflow Tract Obstruction: Results From A Multicenter Registry. Issue 3 (June 2016) - Santoro, Francesco; Ieva, Riccardo; Ferraretti, Armando; Fanelli, Mario; Musaico, Francesco; Tarantino, Nicola; Martino, Luigi Di; Gennaro, Luisa De; Caldarola, Pasquale; Biase, Matteo Di; Brunetti, Natale Daniele
Summary: Background: Left ventricular outflow tract obstruction (LVOTO) may complicate an episode of Takotsubo cardiomyopathy (TTC), potentially leading to cardiogenic shock. Beta‐blockers are considered the most suitable treatment for such complication. Aim of the study: The objective of this study was to evaluate the hemodynamic effects, safety, and feasibility of a selective beta‐blocker ( β 1) with a short half‐life, esmolol, in subjects with a TTC episode. Methods: Ninety‐six consecutive patients with TTC were enrolled in a multicenter registry. The hemodynamic and echocardiographic effects of esmolol (0.15–0.3 mg/kg/min) were analyzed in nine consecutive patients with LVOTO. Clinical course of patients, hemodynamics, days of hospitalization, LV function, and adverse events at follow‐up were recorded. Results: Left ventricular outflow tract obstruction was present in 10 (10.4%) of 96 patients. Patients with LVOTO were older and had higher values of troponin‐I at admission. LV ejection fraction at admission (36.1 ± 8.4%) significantly improved at discharge (51.4 ± 6.9%, P = 0.001). Among patients treated with esmolol infusion, LVOT pressure gradient before treatment was 47.6 ± 16.6 mmHg and after 18.2 ± 2.3 mmHg ( P = 0.0091). Systolic blood pressure decreased from 123.8 ± 29.1 to 112.6 ± 12.7 mmHg ( P = 0.1537). Mean hospital stay was 9 ± 2 days. No adverse events were observed during hospitalization and at follow‐up. Conclusions: Esmolol infusion was temporally associated with reduction in intraventricular gradient and systemic blood pressure in patients with TTC and LVOTO. Further controlled studies are warranted to confirm these preliminary findings.